5x+7-3(2x+9)=2(x-8)-13

Simple and best practice solution for 5x+7-3(2x+9)=2(x-8)-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+7-3(2x+9)=2(x-8)-13 equation:


Simplifying
5x + 7 + -3(2x + 9) = 2(x + -8) + -13

Reorder the terms:
5x + 7 + -3(9 + 2x) = 2(x + -8) + -13
5x + 7 + (9 * -3 + 2x * -3) = 2(x + -8) + -13
5x + 7 + (-27 + -6x) = 2(x + -8) + -13

Reorder the terms:
7 + -27 + 5x + -6x = 2(x + -8) + -13

Combine like terms: 7 + -27 = -20
-20 + 5x + -6x = 2(x + -8) + -13

Combine like terms: 5x + -6x = -1x
-20 + -1x = 2(x + -8) + -13

Reorder the terms:
-20 + -1x = 2(-8 + x) + -13
-20 + -1x = (-8 * 2 + x * 2) + -13
-20 + -1x = (-16 + 2x) + -13

Reorder the terms:
-20 + -1x = -16 + -13 + 2x

Combine like terms: -16 + -13 = -29
-20 + -1x = -29 + 2x

Solving
-20 + -1x = -29 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-20 + -1x + -2x = -29 + 2x + -2x

Combine like terms: -1x + -2x = -3x
-20 + -3x = -29 + 2x + -2x

Combine like terms: 2x + -2x = 0
-20 + -3x = -29 + 0
-20 + -3x = -29

Add '20' to each side of the equation.
-20 + 20 + -3x = -29 + 20

Combine like terms: -20 + 20 = 0
0 + -3x = -29 + 20
-3x = -29 + 20

Combine like terms: -29 + 20 = -9
-3x = -9

Divide each side by '-3'.
x = 3

Simplifying
x = 3

See similar equations:

| 2m+1*5= | | 4(2x+4)-20=12 | | 2(a-8)=10 | | r-ll/3=-7 | | -3(5t-4)+5t=7t-7 | | 2w+4-(3w+6)= | | -75=3g | | 20=-5/3z | | 3p*1/3=114 | | (u-10)*6=48 | | 3*1/3p=114 | | x*log(x)=600000000 | | -2.4n-3+(7.8n+2)= | | Y=-1/2x-12 | | -.5(8x-6)=6x-7 | | 10+6+3x=7*3.5 | | -2m(1+4m)5=-13 | | 2(2l-3+l)=36 | | -(3/x)=0 | | 13/6-1/2 | | 10+4+3x=7*3.5 | | 24.5=2.5-4c | | 7+7y=12x-56 | | -(3/x)0 | | 7v^2+224=-84v | | 10x+20y=360 | | a(n-5)+6=bn | | 6q+1+(q+11)= | | 16+3x=7*3.5 | | 30-45=18 | | 1.25m*7=43.25 | | 2x^2dy=(3xy-y^2)dx |

Equations solver categories